Development of a novel method utilising dissolution imaging for the measurement of swelling behaviour in hydrophilic matrices - Adam Ward; Karl Walton; Nihad Mawla; Waseem Kaialy; Lande Liu; Peter Timmins; Barbara R. Conway; Kofi Asare-Addo (Elsevier, 2019)
A variety of imaging techniques are currently used within the field of pharmaceutics to help understand and determine a wide range of phenomena associated with drug release from hydrophilic matrix tablets. This work for the first time aims at developing an appropriate testing imaging methodology using a surface dissolution imaging instrument (SDI2) for determining the swelling of whole compacts using hypromellose as a model hydrophilic matrix former. The influence of particle morphology (CR and DC grades) and two compressional forces (5 and 15 kN) on the initial swelling behaviour of hypromellose were investigated. The results showed that a lower absorbance of 50 mAu with a wider measurement zone proved successful in determining the edge of the gel layer and growth measurements in real-time with high level of details under flow. Despite the differences in the morphology of the grades of hypromellose tested, it was however discovered that gel growth was statistically similar between them which may be attributed to their similar chemistry. This novel method also highlighted differences in the hydrated polymer's appearance which may have been as a result of differences in porosity and solid fraction. This information is of great importance to a formulator as gel growth plays a crucial role in determining drug release from polymer compacts. Keywords: HPMC, Hypromellose, Surface dissolution imaging, Swelling